REPRESENTASI SOSIAL MELALUI PENDEKATAN ILUSTRASI SIMBOLIK PADA POSTER NO WAR - Eston Kamelang Mauleti; Irwan Harnoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
Social events are part of human life, peace, conflicts occur one after another. At the end of February 2022 the world was shocked by the Russian military attack on Ukrainian territory. The world community hopes Russia can stop the attack but it still happens. In March 2022 Japan's Ogaki Poster Museum summoned poster artists (poster call) around the world to participate in voicing their opinions through art posters with the NO WAR theme, in response to the events above. The author of the article responded to this call by sending 2 posters that represented this social problem through a symbolic illustration approach on the poster. The selection through a symbolic illustration approach is considered appropriate because it can have a complex context so that the message conveyed easily and quickly reaches the audience. To underlie the design of symbolic illustrations, research and design methods are used, namely, Components of Illustration Media consist of 4 stages, namely Context, Encoders, Code, and Decoder. Key words : Social events are part of human life, peace, conflicts occur one after another. At the end of February 2022 the world was shocked by the Russian military attack on Ukrainian territory. The world community hopes Russia can stop the attack but it still happens. In March 2022 Japan's Ogaki Poster Museum summoned poster artists (poster call) around the world to participate in voicing their opinions through art posters with the NO WAR theme, in response to the events above. The author of the article responded to this call by sending 2 posters that represented this social problem through a symbolic illustration approach on the poster. The selection through a symbolic illustration approach is considered appropriate because it can have a complex context so that the message conveyed easily and quickly reaches the audience. To underlie the design of symbolic illustrations, research and design methods are used, namely, Components of Illustration Media consist of 4 stages, namely Context, Encoders, Code, and Decoder. Key words : Social, symbolic illustrations, posters